Pink October treasure hunt 2025 - Abdul Rashid, Nor Faezan; Ab Mumin, Nazimah; Othman, Suraya; Osman, Nora Julianna; Ahmad Nasir, Fatimah Najwa; Mohd Radzuan, Thania; Ramli Hamid, Marlina Tanty; Humaira, Syafaf; Ananda Dorai, Madhumathi; Zamridin, Nur Hidayah; Abdul Hamid, Muhammad Syamil; Kamil, Khidir (Faculty of Medicine, 2025)
Breast cancer month is celebrated all over the world in a month of October. For Hospital Al-Sultan Abdullah (HASA), the breast cancer awareness month began with its official launch on 1 October 2025 and concluded in style with the first-ever Treasure Hunt 2025.